2016
DOI: 10.1016/j.virol.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The dengue virus non-structural protein 1 (NS1) is secreted efficiently from infected mosquito cells

Abstract: Dengue virus NS1 is a glycoprotein of 46-50kDa which associates as a dimer to internal and cytoplasmic membranes and is also secreted, as a hexamer, to the extracellular milieu. However, the notion exist that NS1 is secreted only from infected vertebrate and not mosquito cells. In this work, evidence is presented showing that NS1 is secreted efficiently by infected mosquito cells. NS1 was detected in cell supernatants starting at 6hpi with a continuous concentration increase up to 24hpi. Nevertheless, cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…These results are consistent with a study in which mutation of Asn130 resulted in a loss of hexameric NS1 and an increase in the formation of higher-order NS1 oligomers (34). Indeed, our data agree with recent studies showing that NS1 secreted from DENV-infected C6/36 cells is hexameric in nature (51). …”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with a study in which mutation of Asn130 resulted in a loss of hexameric NS1 and an increase in the formation of higher-order NS1 oligomers (34). Indeed, our data agree with recent studies showing that NS1 secreted from DENV-infected C6/36 cells is hexameric in nature (51). …”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found smaller particles with a diameter of 13.1±2.1 nm, which had either electron-translucent or electron-dense cores. Presumably, they could represent either: a) glycoprotein aggregates, similar to the "classic" flavivirus nonstructural protein 1, which is secreted from infected cells (36,37), b) protein structures appearing after long-term persistence, c) virions with incomplete genome, or d) other unknown structures present in IRE/CTVM19 cells. Further investigations are needed to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the DENV NS1 protein was not only secreted from vertebrate cells, but that was also efficiently secreted from mosquito cells lines [7,8]. The secretion of NS1 in vertebrate cells follows the classical Golgi-pathway [9].…”
Section: Introductionmentioning
confidence: 99%